Nuclear mRNA Export Requires Complex Formation between Mex67p and Mtr2p at the Nuclear Pores - Santos-Rosa, Helena; Moreno, Horacio; Simos, Geōrgios; Segref, Alexandra; Fahrenkrog, Birthe; Panté, Nelly; Hurt, Ed (Molecular and cellular biology, 1998)
We have identified between Mex67p and Mtr2p a complex which is essential for mRNA export. This complex, either isolated from yeast or assembled in Escherichia coli, can bind in vitro to RNA through Mex67p. In vivo, Mex67p requires Mtr2p for association with the nuclear pores, which can be abolished by mutating eitherMEX67 or MTR2. In all cases, detachment of Mex67p from the pores into the cytoplasm correlates with a strong inhibition of mRNA export. At the nuclear pores, Nup85p represents one of the targets with which the Mex67p-Mtr2p complex interacts. Thus, Mex67p and Mtr2p constitute a novel mRNA export complex which can bind to RNA via Mex67p and which interacts with nuclear pores via Mtr2p.
Elektronische Reproduktion der Druck-Ausgabe 28. März 2023
Gesehen am 01.12.2025